PEMBELAJARAN KUANTUM TERHADAP KEMAMPUAN BERHITUNG ANAK AUTIS - WIDIASTUTIK, (Jurnal Pendidikan Khusus, 2015)
ABSTRACT   Based on the observation in SLB Dharma Wanita Ujung Pangkah Gresik there were children with autism who had difficulty in counting ability. To enhance counting ability of children with autism could use quantum learning. This research had purpose to analyze whether there was influence of quantum learning toward counting ability to children with autism in SLB Dharma Wanita Ujung Pangkah Gresik. The learning used in this research was quantum learning. The kind of research was pre experiment. The design used the one group pre test and post test. The method used to collect the data was test method. For data analysis this research used analysis technique of statistic non parametric with the subject 6 children with autism. The research result after giving pre test indicated that the children’s average value was 32 and they were then given intervention 8 times with time allocation 2x30 minutes for each meeting and then they were given post test which indicated that there was change, the children’s value was better with the average value 7,66. From the research result it was analyzed using sign test formula (Zh) with Z table 5% two sides test 1,96. The value obtained in counting was ZH = 2,04 so that it could be concluded that “there was significant influence of learning quantum toward counting ability to autism children in SLB Dharma Wanita Ujung Pangkah Gresik”, with the value Zh = 2,04 > Z table 5% = 1,96.   Keywords : Quantum learning, Counting ability